2022
DOI: 10.3389/fmicb.2022.872067
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tick-Borne Karshi Virus Implies Misinterpretation of the Tick-Borne Encephalitis Virus Seroprevalence in Northwest China

Abstract: Despite few human cases of tick-borne encephalitis virus (TBEV), high rates of TBEV seroprevalence were reported among humans and animals in Xinjiang Uygur Autonomous Region in Northwestern China. In this study, the Karshi virus (KSIV) was identified and isolated from Hyalomma asiaticum ticks in Xinjiang. It belongs to the genus Flavivirus of the family Flaviviridae and is closely related to TBEV. KSIV infects cell lines from humans, other mammals and ticks, and causes encephalitis in suckling mice. High minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Researchers successfully isolated virus particles from Hy. asiaticum and then found KSIV in local domesticated sheep and wild-caught greater gerbils ( Lvov et al, 1976a ; Bai et al, 2022 ). They also demonstrated the existence of serological cross-reactivity between TBEV and KSIV, with the antibodies against these two viruses that could recognize each other’s antigens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers successfully isolated virus particles from Hy. asiaticum and then found KSIV in local domesticated sheep and wild-caught greater gerbils ( Lvov et al, 1976a ; Bai et al, 2022 ). They also demonstrated the existence of serological cross-reactivity between TBEV and KSIV, with the antibodies against these two viruses that could recognize each other’s antigens.…”
Section: Resultsmentioning
confidence: 99%
“…In focusing on emerging TBVs, it is important to identify them from closely related viruses of the same viral family. Bai et al found that the epidemic of KSIV can lead to misinterpretation of the high seroprevalence of TBEVs, which can cause misjudgment of the prevalence of TBVs and the degree of risk to humans ( Bai et al, 2022 ). In addition to the proliferation of virus species, the vectors of some TBVs also changed such as CCHFV, TBEV and SFTSV, especially the species of ticks carrying SFTSV increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the virus-containing mouse brain homogenates were incubated with susceptible cell lines, and these viruses from cell culture were obtained (unpublished data). Of these viruses, three strains of CCHFV, four strains of TAMV, and one strain of KSIV were characterized for etiologic properties, pathogenicity, and prevalence in our previous studies [30,32,35,36]. Symptoms and the timeline of disease onset of the mouse groups, which were confirmed for CCHFV, TAMV, and KSIV isolation, are summarized in Table 2 and Fig 4 . Generally, only a few of these mice showed transient symptoms (malaise) in the F1 generation, from which CCHFV and TAMV were isolated in the subsequent generations, while none of the mice had transient symptoms for KSIV (Table 2).…”
Section: Characterization Of Onset Time and Incidence Of Transient An...mentioning
confidence: 91%
“…The brains of diseased mice collected from the F1-F3 generations were selected for metagenomic sequencing, as described in previous studies [9,30]. Successful isolation of different viruses was indicated by further isolating the viruses from the brain homogenates using cell lines, as described in previous studies [32][33][34], and by obtaining full genome sequences of viruses in the brain tissues. The full-genome sequences of viruses isolated from ticks using this method were deposited in GenBank under the following accession numbers: KY354080-KY354082; MG659722-MG659727; MH688511; MT815989-MT815994; MT248418-MT248421; MH688532; MH688535; MH688538-MH688539; and MH688513-MH688517.…”
Section: Data Recording and Analysismentioning
confidence: 99%
“…For example, TBEV, a burden for human health, could be sometimes mistaken for Looping Ill virus (LIV), causing severe conditions mainly in sheep 82 . Bai et al, were led to reconsider high values of TBEV seroprevalence because of the discovery of Karshi virus' circulation in China 118 .…”
Section: Diagnostic Tests: Current Versus Past Infectionsmentioning
confidence: 99%